2016
DOI: 10.1080/17474086.2016.1245137
|View full text |Cite
|
Sign up to set email alerts
|

Can we prevent venous thrombosis with statins: an epidemiologic review into mechanism and clinical utility

Abstract: Statins may be causally associated with a decreased risk of venous thrombosis. If so, this could be a substantive breakthrough since statins do not increase the risk of bleeding and could therefore be used as a safer antithrombotic drug. However, scepticism exists on the observed reduction of venous thrombosis by statins, as it may have been confounded by healthy user effects or other biases. Areas covered: The main focus of this review will be the biases that may have arisen in clinical studies that investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…It has been postulated that modulation of fibrin clot structure and function represents an additional beneficial effect of this widely used medications that have been shown to reduce the risk of VTE [87]. …”
Section: Antithrombotic Agents and Fibrin Clot Propertiesmentioning
confidence: 99%
“…It has been postulated that modulation of fibrin clot structure and function represents an additional beneficial effect of this widely used medications that have been shown to reduce the risk of VTE [87]. …”
Section: Antithrombotic Agents and Fibrin Clot Propertiesmentioning
confidence: 99%
“…It is also correlated with higher levels of factor VIII. Despite this, hsCRP does not appear to be a driving factor of thrombus formation (43). It is also not clear the ordering of VTE and inflammation despite an association between the two.…”
Section: Statins and Inflammationmentioning
confidence: 87%
“…Inhibition of NOX2 activation causes downstream effects via platelet thromboxane A2 (TxA2) and 8-iso-PGF2alpha formation (47). In vitro studies support this idea with mechanisms that include TxA2 (43), however, the Statins Reduce Thrombophilia trial (START) investigated the effect of rosuvastatin on TxA2-mediated platelet activation and found that it is unlikely that this is the etiology (43). Another mechanism may involve peroxisome proliferator activated receptors that are involved in inflammatory responses (47).…”
Section: Statins and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them are observational studies and were performed in selected populations of patients with CVD. 81 The only RCT supporting the effect of statins on decreasing VTE risk was published in 2009. In the JUPITER trial, 13 17,802 apparently healthy individuals, with normal cholesterol levels, were randomized to receive rosuvastatin at 20 mg per day or placebo and were followed for a median period of 1.9 years.…”
Section: Statins To Prevent First Venous Thromboembolismmentioning
confidence: 99%